Infant feeding and allergy. Issue 4 (April 1988) - Miskelly, F G; Burr, M L; Vaughan-Williams, E; Fehily, A M; Butland, B K; Merrett, T G
Abstract : The effect of withholding cows' milk was examined in 487 infants at high risk of allergic disease. Before birth they were randomly allocated either to a control group, most of whom received cows' milk preparations, or to an intervention group, who were offered a soya based substitute. Eczema and wheezing occurred to a similar extent in the two groups during the first year of life, although napkin rash, diarrhoea, and oral thrush were commoner in the intervention group, especially during the first three months. Breast feeding for any length of time was associated with a reduced incidence of wheezing and diarrhoea.